To save her life : disappearance, deliverance, and the United States in Guatemala - Saxon, Dan, 1958- (University of California Press, 2007)
Part human rights drama, part political thriller, part love story, this riveting narrative chronicles the disappearance of one woman as it tells the larger story of the past fifty years of violence and struggle for social justice and democracy, and U.S. intervention in Guatemala. Maritza Urrutia was abducted from a middle-class neighborhood while taking her son to school in 1992. To Save Her Life tells the story of her ordeal which included being interrogated in secret by army intelligence officers about her activities as part of a political opposition group. Chained to a bed, blindfolded, and.